Journalism and medialogy: institutional aspects of the synthesis of media sciences - Potrebin, Andrei V. (Journal of the Belarusian State University. Journalism, 2022)
The article deals with the problem of accuracy considering the definition of a group of scientific disciplines, which study journalism and the media. The research is based upon scientific publications of 2010–2019, containing conceptual judgments and discussions about the content and its use in the Russian academic discourse. The article esteems the understanding of journalism as an institution of society, attempts to distinguish areas of research within the frameworks of the theoretical journalism, medialogy and media theory throughout their connection, acknowledges the need to study both journalism, its norms and principles, and the media system and media environment, thus outlining the opportunity to remove the contradiction between the three identified concepts of journalism and media development.